Sifat Penghakiman dalam Kehidupan Kristen: Menemukan Keseimbangan Antara Keadilan dan Kasih - Ayunike Waoma; Aprianus Ledrik Moimau (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
Judgment is often viewed as a frightening and controversial concept in Christian life. However, when properly understood, judgment is a manifestation of God's justice and love. In Christian living, it is important to strike a balance between justice and love in judgment. Justice is necessary to uphold moral standards and maintain order, while love teaches forgiveness and compassion. By embracing both, Christians can create an environment that is fair yet understanding, while still adhering to the principles of faith.